Wireless Sensor Networks in a Vehicle Environment - Basso, Rafael (My University, 2009)
A wireless sensor network is composed of autonomous distributed sensors that cooperate to monitor physical conditions. In a vehicle these conditions can be tire pressure, cargo temperature, trailer door status, presence detection and others. Furthermore, with this technology available in vehicles, many other applications can be implemented for the truck, driver and dispatcher like remote keyless entry, remote control and much more. The final benefits are safer, securer and more efficient operations. The objective of this thesis work carried out at Volvo Technology AB was to implement and evaluate a prototype solution for wireless sensor networks in vehicles. Volvo has developed the Telematics Gateway, which is a device that is installed in the trucks to collect information from the vehicle, log and send this information to a web portal. Therefore the main objective of this project was to integrate wireless sensors with the Telematics Gateway. The technology chosen for the wireless network is Zigbee. In order to have a complete system, wireless sensor prototypes were also developed. Additionally an evaluation was prepared for the hardware and cost needed to incorporate Zigbee networks into the Telematics Gateway circuit board.
Keywords: Datorteknik; Computer Engineering